Do Social Investments by Mining Companies Harm Citizen-State Relations? Experimental Evidence from Burkina Faso. Issue 3 (4th March 2022) - Bezzola, Selina; Brugger, Fritz; Günther, Isabel; Sebhatu, Dawit
Abstract: Do mining companies investing in public infrastructure in their host communities harm citizen-state relations? This study presents results from a survey-based field experiment conducted in two mining areas in Burkina Faso. We test whether informing respondents about investments undertaken by mining companies in domains considered classic government responsibilities affects citizens' legitimating beliefs in their government and their likelihood of political participation. We randomly expose respondents to short audio stories about water infrastructure investments conducted by either a mining company or a municipal government in a fictitious but comparable village. Hearing about private as opposed to public investment leads to worse perceptions of the capacity and the legitimacy of the government in the fictitious village. Yet, the intervention does not affect respondents' legitimating beliefs in their own local government. At the behavioural level, we find that hearing about either public or private investment as opposed to no information at all significantly increases participation in town hall meetings. Our experimental findings suggest that providing citizens in low-income settings information about investment in public infrastructure elsewhere can raise expectations in their own contexts and thereby stimulate citizen-state relations.